Institutional and governance dimensions of flood risk management a flood footprint and accountability mechanism. - Osti, Rabindra; Joshi, Kaushal ([Manila] Asian Development Bank, 2019)
Flood footprint is defined as the potential impacts of floods on different sectors and vice versa. It is useful as a mechanism to guide institutional arrangements and administrative procedures for activities within flood risk zones and in adjoining areas. The paper also discusses a trial study in the Longxi River basin that demonstrates how technical tools could be used to assess the probable change in flood footprint from different risk management scenarios.
Keywords: Natural disasters -- Risk assessment; Electronic books